2021
DOI: 10.1109/tnsre.2021.3114991
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Hip Proprioception Influences Mediolateral Foot Placement During Walking

Abstract: Hip abductor proprioception contributes to the control of mediolateral foot placement, which varies with step-bystep fluctuations in pelvis dynamics. Prior work has used hip abductor vibration as a sensory probe to investigate the link between vibration within a single step and subsequent foot placement. Here, we extended prior findings by applying time and location varying vibration in every step, seeking to predictably manipulate the continuous, step-by-step relationship between pelvis dynamics and foot plac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The models proposed by Wang & Srinivasan Special issue: Effects of aging on locomotor patterns from several other studies on mediolateral control 15,16,17,18,19,20,21,22,23 and to data from one other study on anteroposterior control 13,24 . Jin et al 24 showed that, as for mediolateral foot placement, the anteroposterior center of mass position and velocity in the corresponding direction only provide a good prediction of anteroposterior foot placement, supporting a more parsimonious model for the control of foot placement than the original model 13 .…”
Section: Foot Placementmentioning
confidence: 99%
See 2 more Smart Citations
“…The models proposed by Wang & Srinivasan Special issue: Effects of aging on locomotor patterns from several other studies on mediolateral control 15,16,17,18,19,20,21,22,23 and to data from one other study on anteroposterior control 13,24 . Jin et al 24 showed that, as for mediolateral foot placement, the anteroposterior center of mass position and velocity in the corresponding direction only provide a good prediction of anteroposterior foot placement, supporting a more parsimonious model for the control of foot placement than the original model 13 .…”
Section: Foot Placementmentioning
confidence: 99%
“…Augmented feedback aims to enhance the information used in a feedback process by providing an artificial stimulus enhancing the available sensory information. Augmented proprioception may provide a tool to enhance the degree of foot placement control 21 . Applying timed tendon vibration to either the stance, or the swing leg, depending on what complied with the current center of mass kinematic state, helped to better coordinate foot placement with respect to the center of mass kinematic state 21 .…”
Section: Augmented Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Training ankle moment control may therefore benefit gait stability, and could potentially allow older adults to walk with a more energetically efficient step width (Donelan et al, 2001). In young adults, augmented proprioceptive feedback worked to enhance the degree of foot placement control (Knapp et al, 2021). Perhaps a similar paradigm can be applied for ankle moment control, to improve modulation following foot placement errors.…”
Section: Discussionmentioning
confidence: 99%
“…The current brain-behavior results may suggest that the slow (right) leg hip musculature is the hip that is being "controlled" to enable the ML asymmetry. Others have shown that stance leg hip proprioception affects ML balance (Roden-Reynolds et al, 2015;Arvin et al, 2015;Knapp et al, 2021).…”
Section: Discussionmentioning
confidence: 99%